Major open questions in the hepatitis B and D field - Proceedings of the inaugural International emerging hepatitis B and hepatitis D researchers workshop - Tu, Thomas; Wettengel, Jochen; Xia, Yuchen; Testoni, Barbara; Littlejohn, Margaret; Le Bert, Nina; Ebert, Gregor; Verrier, Eloi R; Tavis, John E; Cohen, Chari (Virology (New York, N.Y.), 2024)
The early and mid-career researchers (EMCRs) of scientific communities represent the forefront of research and the future direction in which a field takes. The opinions of this key demographic are not commonly aggregated to audit fields and precisely demonstrate where challenges lie for the future. To address this, we initiated the inaugural International Emerging Researchers Workshop for the global Hepatitis B and Hepatitis D scientific community (75 individuals). The cohort was split into small discussion groups and the significant problems, challenges, and future directions were assessed. Here, we summarise the outcome of these discussions and outline the future directions suggested by the EMCR community. We show an effective approach to gauging and accumulating the ideas of EMCRs and provide a succinct summary of the significant gaps remaining in the Hepatitis B and Hepatitis D field.